2020
DOI: 10.2495/st200071
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Behaviour and Tick-Borne Disease Risk

Abstract: Lyme disease is the leading tick-borne disease in the USA, with incidences increasing over the past few decades due in part to climate change. Visitors to natural areas involved in nature-based activities are at a heightened risk of Lyme disease exposure. We surveyed 430 visitors in Acadia National Park to understand the personal protective behaviours and associated barriers to adoption, perceived tick-borne disease risk, and travel behaviour. A two-step cluster analysis revealed two visitor segments: adventur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This is likely due to the current abundance of A. americanum being higher in the southern portion of the state and is likely to delay the diagnosis and treatment of pathogens vectored by these less-studied tick species. Both Bayles et al [ 86 ] and Soucy and de Urioste-Stone [ 87 ] also found that the adoption of effective tick prevention measures, such as tick checks, was associated with the perceived risk of tick bites. As the actual risk of tick exposure changes due to shifting tick habitats and abundance, public and professional awareness must be addressed through dynamic communication efforts.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the current abundance of A. americanum being higher in the southern portion of the state and is likely to delay the diagnosis and treatment of pathogens vectored by these less-studied tick species. Both Bayles et al [ 86 ] and Soucy and de Urioste-Stone [ 87 ] also found that the adoption of effective tick prevention measures, such as tick checks, was associated with the perceived risk of tick bites. As the actual risk of tick exposure changes due to shifting tick habitats and abundance, public and professional awareness must be addressed through dynamic communication efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Lin et al [80] developed a thermal comfort model to identify the optimal structural conditions and times of day for forest walks. A growing focus of recreation climatology has examined the impact of climate change on nature-based activities [174][175][176], including those dependent on a narrow range of environmental conditions such as snow for skiing [177,178], as well as how increased pollinosis [179,180], the spread of disease-transmitting insects [181][182][183], and other concerns can pose challenges for people seeking a comfortable experience in nature. Beyond these environmental drivers, in the U.S. and other countries, there is a growing concern about increasing cultural alienation from nature, especially for urban children who may grow up with little familiarity of wild places and the creatures that inhabit them [184,185].…”
Section: Environmentalmentioning
confidence: 99%